Efektivitas Model Pembelajaran Relating, Experiencing, Applying, Cooperating And Transferring (REACT) Dalam Meningkatkan Hasil Belajar Siswa - Gusti Aryani; Tri Ariani; Wahyu Arini (Prosiding Silampari Conference of Life Sciences and Techonology (Silamparilist), 2026)
This study aims to determine the effectiveness of the Relating, Experiencing, Applying, Cooperating, and Transferring (REACT) learning model in improving science learning outcomes of eighth-grade students at MTs Negeri 1 Lubuklinggau. Low learning outcomes are often caused by the learning process that does not connect the material to real-life contexts and the lack of active student involvement. The REACT model presents a contextual learning solution that structures student understanding through five main stages. The research method used was true experimental with a pretest-posttest control group design. The research population included all eighth-grade students of MTs Negeri 1 Lubuklinggau in the 2025/2026 academic year, totaling 288 students, with samples drawn using simple random sampling consisting of two classes: the experimental class (VIII.3) which implemented the REACT model and the control class which implemented the conventional model. The data collection instrument used a learning outcome test in the form of validated essay questions. Data analysis was carried out using a t-test (paired sample t-test). The results showed that there was a significant increase in learning outcomes in the experimental class that implemented the REACT model compared to the control class. The average post-test score of the experimental class was 49.34, significantly higher than the control class at 44.11. Furthermore, the paired sample t-test showed a significance value (2-tailed) of 0.000 < 0.05. Thus, it can be concluded that the REACT learning model is effective in improving student learning outcomes on the material of Earth structure and its development.